2011
DOI: 10.1089/aid.2010.0302
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of TLR2 and TLR4 in Dendritic Cells in Response to HIV Type 1 and Coinfection with Opportunistic Pathogens

Abstract: The ability to trigger an innate immune response against opportunistic pathogens associated with HIV-1 infection is an important aspect of AIDS pathogenesis. Toll-like receptors (TLRs) play a critical role in innate immunity against pathogens, but in HIV-1 patients coinfected with opportunistic infections, the regulation of TLR expression has not been studied. In this context, we have evaluated the expression of TLR2 and TLR4 in monocytes, plasmacytoid dendritic cells, and myeloid dendritic cells of HIV-1 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
48
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 52 publications
7
48
0
1
Order By: Relevance
“…1). As previously reported, 34 flow cytometry and real time RT-PCR show that pDCs can express TLR2 and TLR4, suggesting an important role of these receptors in activating antiviral responses in the pDCs subsets as well as the induction of type I IFN production. Indeed, using functional assays, pDCs were shown to increase the expression of the costimulatory molecule CD80 in response to TLR2 and TLR4 stimulation (Fig.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…1). As previously reported, 34 flow cytometry and real time RT-PCR show that pDCs can express TLR2 and TLR4, suggesting an important role of these receptors in activating antiviral responses in the pDCs subsets as well as the induction of type I IFN production. Indeed, using functional assays, pDCs were shown to increase the expression of the costimulatory molecule CD80 in response to TLR2 and TLR4 stimulation (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…29 Lately, we have also reported that TLR2 and TLR4 expression is increased in DCs from HIV-1-infected patients with opportunistic infections. 34 All of these studies were obtained using cells derived from HIV-1-infected patients that have shown increased response in the presence of TLR ligands. 23 Here, using MDMs or PBMCs from healthy subjects and infected in vitro with HIV-1 and stimulated with specific FIG.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations